Adjuvant endocrine therapy with cyclin-dependent kinase 4/6 inhibitor, ribociclib, for localized hormone receptor-positive/HER2– breast cancer (LEADER) - Laura M. Spring; Lauren Scarpetti; Arielle J. Medford; Andrzej Niemierko; Amy Comander; Therese Mulvey; Lowell Schnipper; Steven J. Isakoff; Beverly Moy; Seth A. Wander; Jennifer Shin; Zanta Ephrem; et al. (npj Breast Cancer)
Abstract Optimal timing and dosing of adjuvant cyclin-dependent kinase (CDK) 4/6 inhibitor in early breast cancer is controversial. This prospective phase II clinical trial investigated tolerability and safety of two ribociclib dosing schedules. Patients with stage I–III hormone receptor-positive (HR+)/HER2– breast cancer on adjuvant endocrine therapy (ET) were randomized to two ribociclib dosing schedules: 400 mg continuous vs 600 mg intermittent, with initiation in early (prior ET < 2 years) vs delayed (prior ET ≥ 2 years) setting. Primary objective was to evaluate safety and tolerability of continuous vs intermittent schedule. Primary endpoint was proportion of patients who discontinued ribociclib before completion of all 12 cycles (measured at 12 months). Recurrence free survival (RFS) and circulating tumor DNA (ctDNA) detection were also evaluated. 81 patients were enrolled. Only six serious adverse events occurred, with no significant difference between treatment arms and no subject deaths. Twenty-five patients (31%) discontinued ribociclib before completion of 12 months, with no significant difference between treatment arms. Ribociclib discontinuation was higher in early vs delayed initiation (36% vs 21%). At median follow-up of 20 months, two patients in the intermittent arm (600 mg; Arm 2) experienced disease recurrence (2-year RFS 97%, 95%CI 88–99%), vs none in the continuous arm (400 mg; Arm 1) (2-year RFS 100%). ctDNA was only identified in the two subjects with recurrent disease at median of 7.5 months prior to radiological recurrence. Ribociclib is a safe and well-tolerated adjunct to adjuvant ET in early-stage breast cancer. Delayed initiation of ribociclib at 400 mg continuous dosing was feasible, better tolerated and associated with promising outcomes. ctDNA detection preceded clinical evidence of recurrence and may be considered as a surveillance tool in breast cancer.